CO2 utilisation in agricultural greenhouses: A novel ‘plant to plant’ approach driven by bioenergy with carbon capture systems within the energy, water and food Nexus - Ikhlas Ghiat (16932564) (2021)
Securing the growing populations' demand for food energy and water whilst adapting to climate change is extremely challenging. In this regard, bioenergy coupled with carbon capture and storage or utilisation (BECCS/U) is an attractive solution for meeting both the population demand, and offsetting CO2 emissions. The purpose of this study is to evaluate the effectiveness of BECCS/U pathways utilising CO2 for agricultural enrichment in enhancing food systems and reducing GHG emissions within the energy, water and food nexus concept. The study bridges negative emissions with CO2 fertilisation within an integrated system. It consists of a source of CO2 represented by a biomass-based integrated gasification combined cycle with carbon capture, a CO2 network for a sustainable CO2 supply, and a CO2 sink characterised by agricultural greenhouses. A techno-economic and environmental analysis of each of these subsystems is conducted, feeding to an overall performance analysis of the integrated BECCS/U pathway. Results reveal synergetic opportunities between the energy, water and food subsectors, whereby CO2 is captured from an energy sub-system and is efficiently utilised to enhance food sub-systems by improving productivity and reducing crop water requirements. Thus, the proposed integrated BECCS/U system is able to improve food availability by enhancing the food system, increasing the yield by 13.8%, whilst reducing crop water requirements by 28%. System outputs resulted in a levelised cost of 0.35 $/kg of agricultural produce when the system is scaled-up, and an abatement of the related environmental burdens throughout the supply chain by achieving negative CO2 emissions of 24.6 kg/m2.year of cultivated land. Other Information Published in: Energy Conversion and Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.enconman.2020.113668